2021
DOI: 10.3390/f12050628
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Defense Responses in Pinus sylvestris Seedlings by Methyl Jasmonate and Response to Heterobasidion annosum and Lophodermium seditiosum Inoculation

Abstract: The induction of defense responses in Pinus sylvestris L. seedlings by methyl jasmonate (MeJA) was investigated in three experiments. Two different MeJA application methods were tested, and induction of defense responses was assayed by seedling inoculation with Heterobasidion annosum (Fr.) Bref. and Lophodermium seditiosum Minter, Staley and Millar. In the first experiment, five-year-old P. sylvestris ramets of one clone were directly treated with MeJA, followed by inoculation with H. annosum. In the second ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Generally, JAs are beneficial to enhance defensive resistance, or stress tolerance, and therefore have broad application potential in agriculture and forestry as anti-stress protective agents. However, the side-effects of MeJA application, such as inducing seedling mortality and reduction height growth, should not be neglected [197,198].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, JAs are beneficial to enhance defensive resistance, or stress tolerance, and therefore have broad application potential in agriculture and forestry as anti-stress protective agents. However, the side-effects of MeJA application, such as inducing seedling mortality and reduction height growth, should not be neglected [197,198].…”
Section: Discussionmentioning
confidence: 99%
“…Jasmonic acid itself and related jasmonates are plant growth regulators linked with stress mediation and, more specifically, resistance to pathogen attacks and herbivores [ 23 , 24 , 25 ]. As reported by Zas et al [ 4 ], Thaler et al [ 11 ], Sabbagh et al [ 7 ] and others, jasmonates are an effective ISR elicitor that can help with plant response to abiotic and biotic stressors.…”
Section: Introductionmentioning
confidence: 99%
“…As reported by Zas et al [ 4 ], Thaler et al [ 11 ], Sabbagh et al [ 7 ] and others, jasmonates are an effective ISR elicitor that can help with plant response to abiotic and biotic stressors. Jasmonates were even shown to work in several studies on pines and other conifers [ 4 , 8 , 24 , 25 , 26 , 27 ]. However, while previous studies have examined ISR‘s importance for plant resistance mechanisms to biotic and abiotic stress, there is a gap in analyzing its impact on conifer species.…”
Section: Introductionmentioning
confidence: 99%
“…The increased expression levels of PmTCP8 and PmTCP11 under mechanical injury suggested that they may be involved in biological processes, such as preventing the invasion of pathogens. SA, MeJA, ETH, H 2 O 2, and ABA are important exogenous exciters that are induced by external stimuli and have an important role in response to stress [48]. Through gene expression levels, it was found that PmTCP7, PmTCP8, and PmTCP11 positively responded to H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%